A new bellflower, Campanula phitosiana sp. nov. (Campanulaceae) from Western Anatolia, Turkey - Yildirim, Hasan; Şentürk, Ozan; Özdöl, Tuğkan; Pi̇rhan Ademi Fahri (Phytotaxa, 2019)
Campanula phitosiana Yıldırım & Şentürk (Campanulaceae) is described as a new species from the Aydın Mountains range in western Turkey. Diagnostic characteristics, a full description, and comprehensive illustrations and microphotographs of the pollens and seeds are provided. Campanula phitosiana is a stenoendemic species distributed along the Aydın Mountain range near the county of Tire in the province of İzmir in Turkey. It is morphologically related to C. andrewsii, C. celsii, and C. topaliana, which all are distributed on rock crevices in Greece. Differences among the related species are given in detail. A preliminary IUCN Red List assessment of the new species is supplied.